Foundation chemistry - "Raffan, John" (Cambridge University Press London, 1988)
Foundation Chemistry covers the fundamental concepts in advanced chemistry. It contains material from the new A level common core for chemistry that covers atomic structure, the use of the mole and relative masses, chemical bonding and energetics, periodicity, and oxidation states.